Euthanasia for what? Attending to the role of stigma in addiction‐related 'intractable suffering' and 'incurability'. (19th December 2017) - Seear, Kate; Fraser, Suzanne
Abstract : Commentary to:The need to exercise caution in accepting addiction as a reason for performing euthanasia